As viagens ferroviárias em Portugal (1845-1896) - Pereira, Hugo José Silveira da Silva (2013)
Between 1852 and 1893 more than two thousand kilometres of railway were built in Portugal, changing the way people travelled across the Kingdom. Before that, travel only took place by river, by sea along the coast or by land where the lack of obstacles allowed it. This new form of transportation shortened distances and thus gave Portuguese travellers more time. Based on contemporary parliamentary debates, the technical opinions of Portuguese engineering (both manuscript in the records of the Ministry of Public Works and published in technical journals) and contemporary fictional literature, this study aims to describe and explain some of the changes to travelling habits in Portugal. We shall see that new habits were brought on by the railway, as well as new concerns and new opportunities, and it quickly became a widely-used public service.